Octave band technique for noise measurement at the source, path, and receiver of gas turbines in oil and gas facilities - Mohd Yunos, Akmal Haziq; Azmir, Nor Azali (Universiti Putra Malaysia Press., 2022)
Noise measurement is essential for industrial usage. However, further attention to preventing noise pollution is needed, especially when working with equipment generating a high noise level, such as gas turbines. This study aims to determine the best way to perform noise measurement and analyze the octave band frequency generated by noise pollution caused by gas turbine equipment. Data from site measurements show that the gas turbines produce more than 85 dB of noise with a Z-weighted measurement. A noise measuring investigation was conducted to obtain the data for the 1/3 octave band. A frequency-domain was used to comprehend the properties of the noise measurement frequency band. The frequency band was classified into three different zones called low, medium, and high frequency, which is useful in noise measurement analysis to identify a viable solution to reduce the noise. Onsite sampling was performed at the source, path, and receiver of three separate gas turbine locations within oil and gas operations. The 1/3 octave band data collection results at the sound source, path, and receiver demonstrate the noise level distribution at the perimeter of gas turbine installations in the low and medium frequency ranges. Most of the high noise frequency range is between 250 Hz and 2 kHz for source, path, and receiver. All acquired values are compared to the Department of Safety and Health (Occupational Safety and Health (Noise Exposure) Regulations 2019 in Malaysia. As a result, oil and gas service operators can monitor and take countermeasures to limit noise exposure at oil and gas facilities.